Мистецтво танцю як транслятор культурної пам’яті в сучасній Україні - Курдупова, Олена Миколаївна; Дегтяр, Лариса Павлівна; Самойлова, Еліна Сергіївна (РДГУ, 2025)
Стаття досліджує художньо-естетичні можливості хореографічного мистецтва в його здатності структурувати і відтворювати культурну пам’ять України на сучасному етапі. Культурну пам’ять охарактеризовано як сукупність носіїв і практик із відтворення національної ідентичності в спільноті. Зазначено, що культурна пам’ять і національна самобутність у мистецтві танцю представлені на різних рівнях за допомогою музично-ритмічних образів і засобів хореографічної виразності. Показано художньо-концептуальні можливості класичної, народної, бальної та сучасної хореографії, відмінність між якими зумовлена особливостями становлення в радянський період, варіативністю залучення українського матеріалу та наближення до подій сучасності, що забезпечує формування культурної пам’яті української нації. Наголошено на тому, що універсальна хореографічна лексика долучається до представленості України в міжнародному контексті, тоді як опора на класичний і сучасний український матеріал відповідає процесам націотворення в Україні.

The aim of the article is to investigate the artistic and aesthetic possibilities of choreographic art in its ability to structure and reproduce cultural memory in Ukraine at the present stage. The methodological basis of the investigation is an art history and cultural studies approach. Within this approach, methods of semiotic, comparative, and historical-genetic analysis were used. Results. The connection between dance art and cultural memory is demonstrated. Cultural memory is characterised as a set of carriers and practices for reproducing national identity in a community. It is emphasised that art has the ability to preserve and interpret cultural memory in artistic images over a long period of time. It is noted that cultural memory and national identity in dance art are represented at different levels through musical and rhythmic images and means of choreographic expression. It is noted that the differences are due to the peculiarities of the trends and conditions of formation in the Soviet period. Ideological control over the training of future specialists and the repertoire of creative groups led to the deformation of Ukrainian imagery, but it contributed to the preservation of cultural memory. The artistic and conceptual possibilities of classical, folk, ballroom and contemporary choreography are demonstrated, the differences between which are determined by the variability of the use of Ukrainian material and the nearness to contemporary events, which ensures the formation of the cultural memory of the Ukrainian nation. Due to the globalised and digitalised world, a universal choreographic vocabulary contributes to Ukraine9s representation in the international context. At the same time, reliance on classical and contemporary Ukrainian material corresponds to the processes of nation building in Ukraine. Scientific novelty lies in the investigation of the artistic representation of cultural memory using the example of choreography and art education in the field of performing arts in modern Ukraine. The practical significance lies in the use of the research results in teaching practical and theoretical disciplines in dance art. The materials can be used in the development of art projects and international dance projects, as well as in further scientific work on the study of the nation-building potential of choreography.
Keywords: перформативні мистецтва; хореографічне мистецтво українське; хореографічна освіта; культурна пам'ять